EVALUATING AND IMPROVING THE QUALITY OF PRIMARY TEACHER EDUCATION: A REVIEW OF RECENT METHODS AND APPROACHES - Komari Komari; Upi Laila Hanum; St. Wijdanah Ram (International Journal of Teaching and Learning, 2025)
Evaluating and improving the quality of primary school teacher education plays an important role in building a strong educational foundation for students. This study uses the literature method. The results show that competency-based evaluation emphasises the assessment of practical skills and theoretical knowledge. Then, competency improvement through technology-based learning, such as the use of Learning Management System (LMS), is vital in providing flexible and interactive training for teachers. The development of social and emotional competencies is also recognised as an important factor, with training programmes integrating teachers' emotional and mental well-being. This overall approach aims to produce primary school teachers who are not only academically skilled, but also have a stable emotional balance, which in turn improves the quality of education in primary schools.